EVALUATION OF WEED CONTROL METHODS ON GROWTH PERFORMANCE OF BAMBARA GROUNDNUT (Vigna subterranea (L.) Verdc) LANDRACES IN SUDAN SAVANNA, NIGERIA - Musa, Muhammad; Lado, A.; Ibrahim, A. M. (FUDMA JOURNAL OF SCIENCES, 2025)
Two field trials were conducted at Teaching and Research Farms Faculty of Agriculture of both BUK and Dutsin-ma (FUDMA) during the 2021 and 2022 rainy season to study the herbicidal potentials of Tithonia diversifolia (hemsley) growth component of bambara groundnut (Vigna subterrenea (l.) verdc) landraces in Sudan savanna of Nigeria... The experiment consisted of three (3) Bambara groundnut landrace (Hawayen Zaki, Idon Bazawara and Ja) and nine (9) weed control methods which were factorially combined and laid out in a split plot design with landraces at the main plot while weed control methods at the sub-plot. Data on growth components were collected and subjected to analysis of variance for Split Plot Design (SPD). F-test was used to test for the level of significance, mean comparison was done using Student Newmans’ Keul (SNK) at P < 0.05, Statistical analysis Software (SAS) version 9.1 was used to analyze the data. Landrace had no significant effect on plant height of bambara groundnut except at DTM in 2021 during the 9WAS sampling period, where hawayen zaki (24.39 cm) and ja (25.27 cm) landraces produced the tallest plant which were statically similar compared to idon bazawara (22.6 cm) landrace which produced the shortest plant. Weed control methods on the other hand significantly influenced   plant height of bambara groundnut at both location, season and sampling periods. Where Pre-emergence application of Tithonia fb imazethapyr 0.5kg ai/ha at 6 WAS produced the tallest plant at both locations across all the sampling periods while the shortest plant was observed...
Keywords: Bambara groundnut; Landrace; Growth; Herbicide; Weed control methods